Study of normal ocular thermogram using textural parameters - Tan, Jen-Hong; Ng, E.Y.K.; Rajendra Acharya, U.; Chee, C. (Infrared physics & technology, 2010)
Ocular surface temperature (OST) has been studied with numerous approach and Infrared (IR) thermography has proved to be the best way to capture temperature distribution over some surfaces. It is applied to a number of biomedical applications including studies in the field of ophthalmology. However, the analysis of an ocular thermogram is largely in nascent stage, and is usually achieved by first-order texture analysis. This current study conducted second-order texture analysis on ocular thermal images, mainly by cross co-occurrence matrix together with first-order texture analysis, moments and difference histogram. It was found that, for subjects aged above 35 years old their interocular difference in median, textural contrast, moment 2 and moment 3 (in absolute value) were significantly higher than younger peers. Several significant linear correlations among investigated features were observed. The features extracted from cross co-occurrence matrix may play an important role in the diagnosis of ocular diseases.